Braving Troubled Waters : Sea Change in a Dutch Fishing Community - van Ginkel, Rob (Amsterdam University Press, 2009)
Dwindling fish stocks, changing markets and often ill-advised government intervention have affected the lives of Dutch fishermen for decades. The author of this study has spent years among the fishermen of the Dutch island of Texel, and this book records the changes in their working lives, tracking the influence of national and international factors on the social and cultural structures of the community.
Onvoorspelbare visvoorraden in zee, de wispelturige markt en de al even grillige staatsinterventies in de visserij zijn dagelijkse kost voor vissers. Rob van Ginkel onderzoekt in Braving Troubled Waters de wijze waarop Nederlandse zeevissers vanaf het begin van de achttiende eeuw tot het heden zijn omgegaan met deze factoren. Hiervoor richt hij zich op het visserijbedrijf op het eiland Texel. Hij laat zien hoe nationale en internationale processen van invloed zijn op de sociaal-culturele structuur van Texel.
English
Keywords: Netherlands; History; Society & culture: general; Sociology & anthropology; Politics & government; Fisheries & related industries; public administration; bestuurskunde; geschiedenis; history, geography, and auxiliary disciplines; anthropology; anthropologie